Implementasi Model Problem Based Learning sebagai Upaya Meningkatkan Hasil Belajar Akuntansi pada Materi Neraca Lajur Peserta Didik Kelas X AKL SMKS Labor Binaan FKIP Universitas Riau Pekanbaru - Aryo Nugroho Pratama, Eka Prasetia Cahyani, Febby Valencia; Renda Mulyana, Wiltri Oktaviani, Nurhuda, Anita Andraini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effectiveness of the implementation of the Problem Based Learning (PBL) learning model in improving the learning outcomes of class X Accounting and Institutional Finance (AKL) students at SMKS Labor Fostered by FKIP Universitas Riau Pekanbaru on the Trial Balance material. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles, with planning, implementation, observation, and reflection stages in each cycle. Learning outcome data were collected through assessment and analyzed quantitatively using the paired samples t-test. The results showed an increase in the average value from 87.15 in cycle I to 94.07 in cycle II. The paired samples t-test statistical test produced a significance value (2-tailed) of 0.002 <0.05, which indicates a significant difference between learning outcomes in cycles I and II. As many as 74.1% of students experienced an increase in value, while the rest maintained or experienced a slight decrease. In addition, students showed an active attitude and positive response to the implementation of PBL. In conclusion, the Problem Based Learning learning model is effective in improving accounting learning outcomes, while encouraging active involvement and critical thinking skills of students. Therefore, this model is recommended to be applied in accounting learning and other subjects.